Studies on micro encapsulation of vanilla extract - SARIGA S; Dr. Prince M.V (Guide) (Tavanur 2015 Department of Food and Agricultural Process Engineering)
Studies on micro encapsulation of vanilla extract
Studies on micro encapsulation of vanilla extract